Potential Community Capacity and Factors Related Dengue Control in Developing a Sustainable Dengue Hemorrhagic Fever Control Model in a High Endemic Area, Semarang, Indonesia - Siyam, Nur; Martini, Martini; Wahyuningsih, Nur Endah; Adi, Mateus Sakundarno (Public Health of Indonesia, 2025)
Background: Community participation has been widely recognized as a key determinant of successful and sustainable dengue control efforts. Developing a community participation model that aligns with local needs is essential for achieving long-term effectiveness. However, limited information on the capacity and engagement of both community leaders and non-leaders in high-endemic areas has hindered optimal model development due to the lack of supporting evidence. Objective: This study aimed to assess the potential capacity of the community and to identify factors associated with dengue control efforts, as part of developing a sustainable dengue prevention model in a high-endemic setting in Semarang, Indonesia. Methods: A total of 107 households, consisting of both community leaders and non-leaders, were included in this study. Data were collected using a structured questionnaire through a household survey employing a quantitative approach. Results: The findings indicated that the highest levels of community capacity were observed in health service providers (81.9%), community participation (81.7%), and network awareness among regional leadership groups (80.7%). Key stakeholder contributions were most prominent in disseminating information or knowledge (81.1%), engaging in community activities (79.1%), and providing supporting facilities and infrastructure (75.7%). The development of an effective dengue control model must take into account perceived susceptibility to dengue, self-efficacy, social mobility, and paternal involvement. Conclusion: The development of community-based dengue control models must be aligned with existing community capacities. Policymakers should strengthen dengue control strategies by optimizing both well-established and currently underutilized community assets to enhance program effectiveness and sustainability. Keywords: cadre; community leader; father involvement; household control; stakeholder engagement